A robot-aided visuo-motor training that improves proprioception and spatial accuracy of untrained movement - Elangovan, Naveen (2018)
Proprioceptive function can become enhanced during motor learning. Yet, we have incomplete knowledge to what extent proprioceptive function is trainable and how a training that enhances proprioception may infuence performance in untrained motor skills. To address this knowledge gap, healthy young adults (N=14) trained in a visuomotor task that required learners to make increasingly accurate wrist movements. Using a robotic exoskeleton coupled with a virtual visual environment, participants tilted a virtual table through continuous wrist fexion/extension movements with the goal to position a rolling ball on table into a target. With learning progress, the level of difculty increased by altering the virtual ball mechanics and the gain between joint movement and ball velocity. Before and after training, wrist position sense acuity and spatial movement accuracy in an untrained, discrete wrist-pointing task was assessed using the same robot. All participants showed evidence of proprioceptive-motor learning. Mean position sense discrimination threshold improved by 34%. Wrist movement accuracy in the untrained pointing task improved by 27% in 13/14 participants. This demonstrates that a short sensorimotor training challenging proprioception can a) efectively enhance proprioceptive acuity and b) improve the accuracy of untrained movement. These fndings provide a scientifc basis for applying such somatosensory-based motor training to clinical populations with known proprioceptive dysfunction to enhance sensorimotor performance.